Analisis Nilai pH dan Tingkat Kerusakan Silase Pakan Komplit yang Diformulasi Dengan Daun Lamtoro (Leucaena leucocephala) Sebagai Pakan Ternak Ruminasia - Qadarullah, M Nurul; Munir, Munir; Irmayani, Irmayani (Fakultas MIPA UNM, 2019)
Abstract. The purpose of this study was to determine the effect of adding lamtoro leaves (leucaenanleucocephale) on pH values and the level of damage at different levels. This study used a completely randomized design (CRD) with 4 treatment levels and 3 replications, namely J0= lamtoro leaf 0%, J1= addition of lamtoro leaves 40%, J2=addition of lamtoro leaves 30%, J3=addition of lamtoroleaves 20%. The results showed that the addition of lamtoro leaves to feed silage has a very real effect. on average the highest to lowest pH value is J0 is (5.16), J1 is (3.83), J2 is (4.67), and J3 is (4.73). Average damage to the highest to lewest is J0 is (6.67), J1 is (1.76), J2 is (4.38), and J3 is (4.78). From the results of the study, it is known that the best treatment and recommended defects are J1 treatment with the addition of lamtoro leaves 40%. Keywords: pH, damage rate, complete feed silage, lamtoro leaf, and rice strawid